2013
DOI: 10.1021/am4003364
|View full text |Cite
|
Sign up to set email alerts
|

Interaction and Release of Catechin from Anhydride Maleic-Grafted Polypropylene Films

Abstract: In this paper, investigations were carried out on catechin-loaded maleic anhydride (MAH)-modified polypropylenes (PP). Two maleic-modified polypropylenes (PPMAH) with different maleic concentrations have been blended with PP and catechin to obtain composites of improved catechin retention with the aim of studying the possible interactions between these grafted polymers with antioxidants, and a secondary interest in developing an active antioxidant packaging. Composite physicochemical properties were measured b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 40 publications
(64 reference statements)
1
24
0
1
Order By: Relevance
“…This unexpected results can be related with the fact that flavonones mainly interact with polymeric matrices by hydrogen bonding interactions between hydroxyl groups and carbonyl groups of the polymeric matrices, which are not present in PP. In this sense, de Dicastillo et al blended maleic anhydride modified poly(propylene) (MAPP) with flavonoids and found the formation of intermolecular hydrogen bonds due to the maleic anhydride modification on polypropylene which allowed hydrogen bonding interactions between hydroxyl groups of catechin and carbonyl groups of MAPP . Slightly higher OIT values were found when the PP was blended with p ‐coumaric, trans‐ferrulic and chlorogenic acids, resulting in 1.1, 1.2, and 1.9 min, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This unexpected results can be related with the fact that flavonones mainly interact with polymeric matrices by hydrogen bonding interactions between hydroxyl groups and carbonyl groups of the polymeric matrices, which are not present in PP. In this sense, de Dicastillo et al blended maleic anhydride modified poly(propylene) (MAPP) with flavonoids and found the formation of intermolecular hydrogen bonds due to the maleic anhydride modification on polypropylene which allowed hydrogen bonding interactions between hydroxyl groups of catechin and carbonyl groups of MAPP . Slightly higher OIT values were found when the PP was blended with p ‐coumaric, trans‐ferrulic and chlorogenic acids, resulting in 1.1, 1.2, and 1.9 min, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In this sense, de Dicastillo et al blended maleic anhydride modified poly(propylene) (MAPP) with flavonoids and found the formation of intermolecular hydrogen bonds due to the maleic anhydride modification on polypropylene which allowed hydrogen bonding interactions between hydroxyl groups of catechin and carbonyl groups of MAPP. [38] Slightly higher OIT values were found when the PP was blended with p-coumaric, transferrulic and chlorogenic acids, resulting in 1.1, 1.2, and 1.9 min, respectively. The higher antioxidant protection provided by these antioxidants could be related with their longer aliphatic chains which allowed higher molecular mobility and thus facilitating their interaction with PP polymeric matrix.…”
Section: Thermal Propertiesmentioning
confidence: 96%
“…When comparing the IR spectra of the films to those of the neat components (PP, HNTs and carvacrol), no evident shifts in the characteristic peaks are observed, see Figure 2. As the sensitivity of the FTIR may be insufficient to characterize such interactions [58] if they exist, we have employed molecular dynamics (MD) simulations as a tool to study the interactions between the nanocomposite components.…”
Section: Resultsmentioning
confidence: 99%
“…Migration studies were conducted at 40 °C in accordance with European Union regulations. Double‐sided, total immersion migration tests were performed as follows: a 3‐cm 2 piece of each film and 5 mL of simulant (area‐to‐volume ratio around 6 dm 2 /L) were placed in a glass vial, and periodically, the release of active agents were measured indirectly as the antioxidant activity of food simulants through 2,2‐azinobis(3‐ethylbenzothiazoline‐6‐sulfonic acid) (ABTS) method …”
Section: Methodsmentioning
confidence: 99%